To evaluate the expression, we substitute the given values into the expression:
StartFraction y z over w EndFraction + 2 x
Substituting w = 3, x = -2, y = 6, and z = 0.5:
StartFraction 6 times 0.5 over 3 EndFraction + 2 times -2
Simplifying:
StartFraction 3 + (-4) EndFraction
3 - 4 = -1
Therefore, the expression evaluates to -1.
Evaluate the expression when w = 3, x equals negative 2, y = 6, and z = 0.5.
StartFraction y z over w EndFraction plus 2 x
(1 point)
Responses
5
5
negative 3
Image with alt text: negative 3
negative 4
Image with alt text: negative 4
0
1 answer